Fixation of the Proximal Metatarsal Crescentic Osteotomy Using a Head Locking X-Plate. (February 2016) - Pauli, Werner; Koch, Axel; Testa, Enrique; Dopke, Kai; Perry, Philip; Honigmann, Philipp
Background: We present a new method to stabilize proximal crescentic osteotomies (PCOs) for the correction of moderate to severe hallux valgus. Methods: A single-center prospective study with a consecutive series of 72 patients (94 feet) with a PCO was performed using a head locking X-plate. The primary aim was to investigate the stability of the osteotomy, measuring the dorsal elevation of the first metatarsal head, first cuneiform height, talus–first metatarsal angle, and first metatarsal inclination pre- and postoperatively. A secondary outcome assessed weight distribution during gait, quality of life, and radiologically documented bone healing process. Results: Ninety-three percent of the feet were within ±2 mm change for dorsal elevation of the first metatarsal head, and 72% for the medial cuneiform height. Eighty-nine percent were within ±4 degrees change for the first metatarsal inclination, 73% for the talus–first metatarsal angle, and 100% for the calcaneus pitch angle. The mean changes between pre- and 1-year postoperative were not significantly different for any of the stability measurements except for the first metatarsal inclination angle. The SF36 showed a significant improvement of physical function, general health, and decreased bodily pain. Harris mat footprints showed a decrease of 46% underneath the second and a pressure decrease of 40% underneath the third metatarsal head. Conclusion: This technique, of using a head locking X-plate to stabilize the PCO, showed satisfactory and reproducible results in terms of stability, clinical outcome, bone healing, and patient satisfaction. The plate provided substantial support for the PCO resulting in adequate and easy fixation. Level of Evidence: Level IV, retrospective case series.